High-energy Li-ion hybrid supercapacitor enabled by a long life N-rich carbon based anode. (20th September 2016) - Sun, Fei; Gao, Jihui; Liu, Xin; Wang, Lijie; Yang, Yuqi; Pi, Xinxin; Wu, Shaohua; Qin, Yukun
Graphical abstract: Highlights: N-rich carbon spheres (NRCS) are synthesized by a continuous spraying process. NRCS exhibits excellent performance as LIBs anode materials. Hybrid supercapacitor exhibits high energy and power densities and long cycle live. Abstract: Hybridizing battery and capacitor materials to construct hybrid supercapacitors has been regarded as a promising avenue to achieve high energy densities while maintaining high power-output. Herein, we report a lithium ion hybrid supercapacitor with high power and energy densities as well as excellent cycling stability, which is constructed of an N-rich carbon based anode and commercial activated carbon cathode. The N-rich carbon spheres (NRCS) possess high surface area, uniform mesoporous structure, and high level of N-doping, synergically enabling excellent lithium storage properties in terms of high capacity, fast rate capability and long cycling lifespan even at high current rate (638 mAh g −1 after 2000 cycles at 2 A g −1 ). Benefitting from above merits of NRCS, the assembled hybrid supercapacitor delivers a high energy density of 105.8 W h kg −1 at 650 W kg −1 . Even when power density increases to 10800 W kg −1, 40.4 W h kg −1 can be maintained. Long cycling life (capacity retention of 75% after 8000 cycles) is also demonstrated. This work offers a new platform for high-energy hybrid supercapacitors by assembling high-performance porous carbon based anode.